Mitigação de ataques de negação de serviço em rests autenticáveis na nuvem - Michelin, Régio Antonio (2015)
Computer systems available on the Internet are used for, basically, everyone. This widespread use has facilitated their exposure to several different types of attacks. These attacks are intended to, for example, steal information, deploy malicious code and even to make a system slow to respond, or worst, to become completely offline. Denial of service attacks is a type of attack that, currently, needs a special attention, since they may be performed for different reasons, such as political purposes, industrial competition, protests or even just for fun. This kind of attack has as its main purpose to slow response time or even to make a computer system unavailable, for example, consuming all target computational resources. When a denial of service attack targets a cloud environment, it could compromise not only one system, but also all systems that are hosted in the cloud. Therefore, a cloud environment is a convenient target for malicious users, since that with a single attack they are able to hit multiple systems. A cloud environment usually exposes, through a REST architecture model, an API to allow its users to write their own service to be integrated with the cloud environment. Hence, this exposed REST API becomes a potential threat to the cloud environment. In order to reduce the risk of attacks, usually a cloud environment uses an authentication mechanism to allow only legitimate users to access the system. Despite that, some attacks may still be possible. This research is focused on the analysis of denial of service attacks that exploit the authentication mechanism through REST API calls in a cloud environment. In this work, we propose a solution that works in the application level. Our solution creates client profiles in order to verify whether a client is posing any threat to the cloud or not. When a threat is detected, then our solution starts to filter calls from users that were identified as malicious. We applied our solution to Openstack, an open cloud management system, and showed that we have improved response time for legitimate users when the cloud is under attack.